Ball milling as a mechanochemical technology for fabrication of novel biochar nanomaterials. (September 2020) - Kumar, Manish; Xiong, Xinni; Wan, Zhonghao; Sun, Yuqing; Tsang, Daniel C.W.; Gupta, Juhi; Gao, Bin; Cao, Xinde; Tang, Jingchun; Ok, Yong Sik
Graphical abstract: Highlights: Principles, mechanisms, and fundamentals for biochar ball milling are reviewed. Ball milling is an emerging technology for the production of engineered biochar. Ball-milled biochar shows good performance in environmental and energy applications. Functionalization and sustainability assessment are prospects for future studies. Abstract: Mechanochemical synthesis of nano-biochar by ball-milling technology is gaining attention for the sake of its low-cost and eco-friendly nature. Ball milling as a non-/less-solvent technology can propel environmental sustainability and waste valorization into engineered biochar for advanced applications. Scalable production of biochar nanomaterials with superior properties (e.g., 400–500 m 2 g −1 surface area and 0.5–1000 nm pore sizes) enables diverse applications in the field of energy and environment. This review critically evaluates the synthesis, characterization, and application of ball-milled biochar nanomaterials based on the latest findings. Limitations such as feedstock selection, process optimization, product homogeneity and reusability, environmental risks, and sustainability assessment remain challenging for further studies. This work highlights the recent advances on mechanochemical biochar technology and offer insights into opportunities and future prospects related to sustainable and facile synthesis of biochar-based novel materials for achieving sustainable development goals.